The Possibilities of the Laparoscopic Approach in the Treatment of Endometrial Cancer of Patients with Obesity - A. A. Ishchenko; A. I. Ishchenko; M. A. Klokova; A. V. Kochatkov (Сеченовский вестник, 2015)
The article traces the main features and possibilities of laparoscopic approach in the treatment of endometrial cancer in patients with obesity.